Local order of orthorhombic weberite-type Y3TaO7 as determined by neutron total scattering and density functional theory calculations✰. (1st September 2020) - Gussev, Igor M.; O'Quinn, Eric C.; Baldinozzi, Gianguido; Neuefeind, Jörg; Ewing, Rodney C.; Zhang, Fuxiang; Lang, Maik
Abstract: Weberite-type oxides are a family of oxides with A3 BO7 stoichiometry that can adopt different space groups depending on chemical composition. There is a discrepancy in previous studies as to whether Y3 TaO7 is the orthorhombic C222 1 or the Ccmm space group. Here, we describe the short- and long-range structural properties of weberite-type Y3 TaO7 using neutron total scattering data, which has a high sensitivity to the oxygen sublattice. Simultaneous analysis of both short- and long-range structural data via conventional Rietveld and small box modeling demonstrates that Y3 TaO7 is best modeled as C2221 . While the Ccmm describes equally well the long-range structure, pair distribution function analysis revealed that the local atomic configuration can be best modelled as C2221 . This is corroborated by first-principles calculations that confirm the energetic preference of the C222 1 over Ccmm . Neutron total scattering data are reported for the first time for the Y3 TaO7 weberite-type ceramics. Graphical abstract: Image, graphical abstract